Assessing 21st Century Skills: Development and Validation of a Multidimensional Tool for College Students - Yadav, Namita; Lalita Vatta (Indian Journal of Extension Education, 2026)
This study endeavours to develop and validate a multidimensional tool for the assessment of 21st century skills among college-going students during 2024-25 at Banaras Hindu University (BHU), Varanasi. Initially, 120 items were identified through a comprehensive literature review. Experts from the teaching and research domains reviewed these items, and their feedback was incorporated to refine the tool, resulting in 56 items. The refined tool was administered to 350 respondents. The construct validity was established through exploratory factor analysis (EFA) and subsequently confirmed through confirmatory factor analysis (CFA) to ascertain the adequacy of the model fit. EFA revealed that the seven-factor structure accounted for a substantial proportion of the total variance. The CFA of the 54-item 21st-century skills assessment tool identified seven factors with good internal consistency. CFA indicated that items were loaded on the relevant factors and evidenced satisfactory model fit indices. The reliability of the tool was established by the Cronbach’s alpha coefficient, which yielded a value of 0.81. Thus, the tool was indicated to be relevant for college students and served as a valuable metric to assess college students’ 21st century skills.